Disease-associated mutations within the yeast DNAJB6 homolog Sis1 slow conformer-specific substrate processing and can be corrected by the modulation of nucleotide exchange factors - Ankan K. Bhadra; Michael J. Rau; Jil A. Daw; James A. J. Fitzpatrick; Conrad C. Weihl; Heather L. True (Nature Communications, 2022)
Here the authors describe mechanisms through which analogous LGMDD1 (Limb-Girdle Muscular Dystrophy Type D1) mutations affect Sis1 (a yeast functional homolog of human DNAJB6) chaperone activity and poison the function of wild-type protein; potentially uncovering a new therapeutic route to explore.